Abnormalities in whole-brain functional connectivity observed in treatment-naive post-traumatic stress disorder patients following an earthquake. Issue 9 (July 2014) - Jin, C.; Qi, R.; Yin, Y.; Hu, X.; Duan, L.; Xu, Q.; Zhang, Z.; Zhong, Y.; Feng, B.; Xiang, H.; Gong, Q.; Liu, Y.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Convergent studies have highlighted the dysfunction of the amygdala, prefrontal cortex and hippocampus in post-traumatic stress disorder (PTSD). However, only a few studies have investigated the functional connectivity between brain regions in PTSD patients during the resting state, which may improve our understanding of the neuropathophysiology of PTSD. The aim of this study was to investigate patterns of whole-brain functional connectivity in treatment-naive PTSD patients without co-morbid conditions who experienced the 8.0-magnitude earthquake in the Sichuan province of China. Method A total of 72 PTSD patients and 86 trauma-exposed non-PTSD controls participated in the resting-state functional magnetic resonance imaging study. All these subjects were recruited from the disaster zone of the 2008 Sichuan earthquake. Functional connectivities between 90 paired brain regions in PTSD patients were compared with those in trauma-exposed non-PTSD controls. Furthermore, Pearson correlation analysis was performed between significantly abnormal connectivities in PTSD patients and their clinician-administered PTSD scale (CAPS) scores. Results Compared with non-PTSD controls, PTSD patients showed weaker positive connectivities between the middle prefrontal cortex (mPFC) and the amygdala, hippocampus, parahippocampal gyrus and rectus, as well as between the inferior orbitofrontal cortex and the hippocampus. In addition, PTSD patients showed stronger negative connectivity between the posterior cingulate cortex (PCC) and the insula. The CAPS scores in PTSD patients correlated negatively with the connectivity between the amygdala and the mPFC. Conclusions PTSD patients showed abnormalities in whole-brain functional connectivity, primarily affecting the connectivities between the mPFC and limbic system, and connectivity between the PCC and insula.